A modified Johnson-Cook model of 6061-T6 Aluminium profile. Issue 2 (15th March 2022) - Geng, Guoqing; Ding, Dazhuang; Duan, Libin; Jiang, Haobin
ABSTRACT: The flow behaviour of the 6061-T6 aluminium profile in different specimen directions at different strain rates was studied by the tensile test. The results reveal that the constitutive relation of aluminium profiles exhibits anisotropy and exhibits certain strain rate sensitivity and positive strain rate hardening effect at different strain rates. It is also found that the strain rate hardening effect and strain hardening effect are mutually influential. The constitutive equation established with the original Johnson-Cook (J-C) model failed to predict the stress-strain relationship of aluminium alloy profiles well due to the neglect of this interaction. Thus, based on studying the effect of strain on strain rate hardening effect, the strain rate hardening coefficient of the J-C model is modified. The modified J-C model takes into account the influence of strain on the strain rate hardening effect. The comparison result shows that the modified Johnson-Cook model more accurately predicts the plastic flow process of aluminium profiles.